One branch curve singularities with at most 2-parameter families of ideals - Drozd, Yu.A.; Skuratovskii, R.V. (Algebra and Discrete Mathematics, 2012)
A criterion is given in order that the ideals of a one branch curve singularity form at most 2-parameter families. Namely, we present a list of plane curve singularities from the Arnold's classification which are the smallest among all one branch singularities having at most 2-parameter families of ideals.